Spectral Analysis of Monthly Averages of Geomagnetic Field in Huancayo Observatory (1922 - 1990) - Rojas Acuña, Joel (1999)
Spectral analysis has been applied to time series of monthly mean values of D, H and Z components of the geomagnetic field recorded at the Huancayo Observatory (HMO). The maximum entropy spectral analysis technique, according to the algorithm by J.P. Burg, was used to calculate the coefficients for the errorprediction filter, and Akaike's criteria was used to obtain the length of the error prediction filter. The technique of fast Fourier transform as also applied to the same data with the porpose of comparison with the results obtained with the maximum entropy technique. Polynomials of second and third degrees were fitted to the D and H time series respectively by the least squares method, and a Fourier series with 30 harmonics was fitted to the Z time series. After removal of the tendency, which explains much of the secular variation of internal origin, the residual variations exhibit fluctuations of external origin. The existence of a ~34 year spectral line is resolved very intensely in the D and H records. A period of 10.6 years, related to the solar cycle (11 years) is resolved in D and H, and a period of 26.9 months, related to the quasibiennieal (26 months) is resolved in Z. The annual and semiannual periods are resolved in all the spectra with both methods. Periods of nearly 2.5, 3 and 4 months are detected in all the spectra with both methods. The obtained periods are related to external variations except that of ~34 years which could be the first harmonic of the ~60 year period [11] of internal origin.